Scale of Self-perceived Communication in the Couple Relationship (SCCR) - Iglesias-García, Maria-Teresa; Urbano-Contreras, Antonio; Martínez-González, Raquel-Amaya (Anales de Psicología / Annals of Psychology, 2019)
This study aims to design and validate the Scale of Self-perceived Communication in the Couple Relationship (SCCR) in order to provide a straightforward and useful instrument. 620 persons who were in a couple relationship took part in this study. The sample was divided randomly into two subsamples to study the factor structure of the scale, carrying out a cross-validation by using an exploratory factor analysis (EFA) and a confirmatory factor analysis (CFA). Also, and to verify that the model remained stable taking account of the variable gender, the confirmatory factor analysis was repeated with the women and men subsamples, and a multigroup CFA was carried out to check the factor invariance according to this variable An 8-items scale was obtained, made up with two factors explaining 46.6% of the variance who also reported a good reliability (α = .75), testing the strict invariance according to the gender. This scale might be useful in the field of detection, prevention and intervention of conflict situations in the couple relationship.